Optimization of Echo Views for Percutaneous Device Closure of Pediatric Atrial Septal Defect through the Femoral Vein Guided by Transthoracic Echocardiography without Radiation. (31st October 2020) - Ye, Zankai; Li, Zhiqiang; Yi, Hanlu; Zhu, Yaobin; Sun, Yan; Zhang, Hongju; Li, Pei; Ma, Ning
Abstract : Objectives . This study aimed to explore the selection of views for transthoracic echocardiography-guided transfemoral puncture for the device closure of pediatric atrial septal defect (ASD) without radiation. Methods . Sixty children (29 males and 31 females) were diagnosed with a central ASD, normal heart function, and no other intracardiac deformity. All procedures were performed in a surgical operating room (without radiological equipment) under basic anesthesia; the femoral vein pathway and guidance by only transthoracic echocardiography were used to complete the device closure of the ASD. The subcostal acoustic window and parasternal aorta short-axis views were used to guide the extra stiff wire and catheter into the left atrium. All procedures were performed under the subcostal biatrial section. The sheath entered the left atrium, and the apical four-chamber view was used to monitor the delivery and release of the occluder. Results . Successful closure of the ASD was achieved in all cases. The operating time from the end of the puncture to the release of the occluder was 10.36 ± 3.57 minutes. No other incisions were needed in 60 cases. No occluders were removed, and no residual shunt or pericardial effusions were detected after the procedures, during the non-ICU stay time. The average hospital stay was 2.19 ± 0.58 days. Conclusion . The accurate selection of transthoracic echocardiographic views can better ensure the safety and effectiveness of ASD closure through the femoral vein without radiation in children.